Tiny Hair Tuft: A Clue for Occipital Cephalocele. (27th August 2013) - Hatipoglu, Nevin; Türel, Özden; Hatipoglu, Husem; Engerek, Nuri; Siraneci, Rengin
Abstract: Recurrent meningitis is a rare problem and can be due to alterations in immune system, or craniospinal defect. Any clue either in patient's history or physical examination would be helpful for avoiding unnecessary and tiring tests. Here we present the case of a child with recurrent bacterial meningitis who had an unnoticed hair tuft on the occipital region. The final diagnosis was occipital cephalocele with a rare presentation of a tiny tuft of hair.